Academic “centres,” epistemic differences and brain circulation - ORTIGA, Yasmin Y. (Institutional Knowledge at Singapore Management University, 2018)
This article investigates the factors that shape how migrant academics engage with fellow scholars within their countries of origin. We focus specifically on the mobility of Asian‐born faculty between Singapore, a fast‐developing education hub in Southeast Asia, and their “home” countries within the region. Based on qualitative interviews with 45 migrant academics, this article argues that while education hubs like Singapore increase the possibility of brain circulation within Asia, epistemic differences between migrant academics and home country counterparts make it difficult to establish long‐term collaboration for research. Singapore institutions also look to the West in determining how research work is assessed for tenure and promotion, encouraging Singapore‐based academics to focus on networking with colleagues and peers based in the US and Europe rather than those based in origin countries. Such conditions undermine the positive impact of academic mobility between Singapore and surrounding countries within the region.